Application Of Leaf Fertilizer And Plant Hormones To Accelerate Shoot Cuttings Growth On The Potato Varieties Of Granola Lembang (Solanum tuberosum L.) - Ishartati, Erny; Rehan, Rehan Prasetya (Universitas Muhammadiyah Malang, 2019)
An important factor in the productivity of potatoes is the procurement of quality potato seeds. Procurement of potato seeds can be done several ways, one of which is by cuttings. Giving plant hormones in cuttings can encourage and accelerate the formation of roots, stimulate the formation of new shoots, and increase the number and quality of shoots and roots. This study uses a split plot design factorial with the first factor is the influence of various kinds of leaf fertilizer consisting of 3 levels, namely PAB (AB Mix), PGD (Gandasil D) and PG (Growmore), and the second factor is some natural plant hormones which consists of Z0 (Rootone F / control), Z1 (bamboo shoots), Z2 (coconut water), Z3 (aloe vera) and Z4 (shallots). All treatments were repeated 3 times. The data obtained were analyzed using orthogonal contrast for treatment vs. control testing. F test to determine diversity, if there is diversity of treatment followed by BNJ test level of 5%. Observation variables included: when the roots appeared, plant height, number of leaves, and stem diameter.The results showed that there was no interaction between the administration of leaf fertilizer with extracts of some plant hormones, only that the treatment of the leaves of the gandasil D fertilizer had a very significant effect on plant height parameters, with an average of 6.57 cm. whereas in orthogonal analysis the contrast between control and treatment, control tends to be higher in value.